Evaluation of a video to promote HIV testing in sexual minorities - Francisco Javier Báez Hernández; Vianet Nava Navarro; Miguel Angel Zenteno López; Víctor Manuel Blanco Álvarez; Arelia Morales Nieto; Pedro Trejo Hernández (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To design and evaluate an educational video aimed at promoting HIV testing in gay men from the theoretical perspective of the Nola J. Pender Health Promotion Model. Methods: The design comprised five steps: 1.- Literature search; 2.- Formulation of the educational objective; 3.- Drafting of the script and location of the information in the theoretical components; 4.- Production; and 5.- Evaluation by experts and the target population. Results: The video "Living Without Fear" was produced, which presents the dilemma faced by gay men before taking a HIV test. The content validity index was 0.85, which indicated that the information was adequate and acceptable for promoting the rapid HIV test. Final Considerations: The results contribute to the scientific evidence aimed at promoting healthy behavior. In addition, the video was shown to be an acceptable educational tool.